Can family doctor contracted services facilitate orderly visits in the referral system? A frontier policy study from Shanghai, China. (9th October 2021) - Huang, Jiaoling; Liu, Yan; Zhang, Tao; Wang, Luan; Liu, Shanshan; Liang, Hong; Zhang, Yimin; Chen, Gang; Liu, Chengjun
Abstract: Background: China committed to establishing a family doctor (FD)‐based referral system following the medical reform in 2009. This paper explored the effect of FD on establishing the anticipated system. Methods: Two waves of survey were conducted in Shanghai, China. 2754 and 1995 individuals were sampled in 2013 and 2016 respectively. We compared orderly visiting behaviour between contracted and non‐contracted residents. Logistic regression models were performed to further test the effect of FD on orderly visits. Results: More contracted residents first‐contacted community health service centres (CHSCs; 45.48%) than non‐contracted residents (28.93%). Contracted residents were also more likely to refer to specialists via CHSCs than the non‐contracted (9.84% vs. 2.60%). The odds ratio (OR) for first‐contact at CHSCs by contract status was 1.569 in 2013, but increased to 1.675 in 2016. Being contracted with a FD was associated with referral behaviour, but the OR declined from 2.692 to 2.487 over years. Conclusion: The survey from Shanghai showed that FD had a significant effect on attracting first‐contact at CHSCs and referral via CHSCs; however, the effect on the latter decreased. The effectiveness of the FD role on referral behaviour requires a well‐established referral system, which has not yet been completely achieved in China.